2008
DOI: 10.1111/j.1468-2494.2008.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of moisturizing and firming effects of cosmetic formulations

Abstract: The assessment of cosmetic efficacy is rarely performed in studies comparing different concentrations of active compounds. The aim of the present study was to determine the skin hydrating and the skin firming dose-response effects of cosmetic formulations enriched in compounds derived from algae and fish collagen. A series of factors were studied including the type of formulation (cream or serum), the concentration in active ingredients, the effect of repetitive applications, as well as any residual effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…These findings are in contrast to topical products which should be mostly effective in the skin ageing-encountered superficial dermis and epidermis [36], where improved skin elasticity is predominantly caused by an increase in epidermal hydration [37,38]. Xhauflaire-Uhoda et al [39] investigated anti-wrinkle effects of topically used skin care products. They found no evidence of skin moisturizing after stopping treatment and, moreover, the low increase in skin hydration corresponded to normal newly generated corneocytes from deeper skin layers.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in contrast to topical products which should be mostly effective in the skin ageing-encountered superficial dermis and epidermis [36], where improved skin elasticity is predominantly caused by an increase in epidermal hydration [37,38]. Xhauflaire-Uhoda et al [39] investigated anti-wrinkle effects of topically used skin care products. They found no evidence of skin moisturizing after stopping treatment and, moreover, the low increase in skin hydration corresponded to normal newly generated corneocytes from deeper skin layers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, marine fish-derived collagen has low odor and improved mechanical strength, prerequisites for cosmetic products [8]. Skin-hydrating and skin-firming effects of cosmetic formulations (cream or serum formulations) using collagen derived from fish were evaluated [45]. The result suggested that serum formulations displayed a better moisturizing effect within a short duration [44,45].…”
Section: Marine Fish-derived Collagenmentioning
confidence: 99%
“…Skin-hydrating and skin-firming effects of cosmetic formulations (cream or serum formulations) using collagen derived from fish were evaluated [45]. The result suggested that serum formulations displayed a better moisturizing effect within a short duration [44,45]. The cream formulations appeared to become more active later, particularly following the repetitive applications.…”
Section: Marine Fish-derived Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin moisture was increased by application of marine sponge collagen-containing products (Swatschek, Schatton, Kellermann, Mü ller, & Kreuter, 2002). Cosmetic formulations enriched in fish collagen-derived compounds exerted moisturizing and firming effects during treatment (Xhauflaire-Uhoda, Fontaine, & Pié rard, 2008). Enzymatically prepared fish collagen hydrolysates are mainly composed of oligopeptides and possess antioxidant activity (Jia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%